Humanization of childbirth: meanings and perceptions of nurses - Andrêssa Batista Possati; Lisie Alende Prates; Luiza Cremonese; Juliane Scarton; Camila Neumaier Alves; Lúcia Beatriz Ressel (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To know the meanings attributed to humanized childbirth by nurses of an obstetric center. Method: A qualitative descriptive study was carried out with nurses from a teaching hospital, located in southern Brazil. An operational proposal was used. The participants were six nurses who worked in the service. Results: The humanization of childbirth was understood as a set of practices and attitudes based on dialogue, empathy and embracement; the provision of guidelines; the appreciation of parturients' singularities; the performance of procedures proven to be beneficial to maternal and child health and continuous professional updating. Conclusion: The humanization of birth is still a challenge in professional practice. The role of women, the respect for their rights and the commitment of health professionals are the foundation of the humanization of childbirth.